Optimization of Surveillance Systems in Industrial Areas Using CCTV Design Tools - Wijaya, Koko Lendra; Nurhadi, Hendro (Syntax Corporation, 2025)
Designing CCTV systems presents its own challenges, especially in choosing the right and accurate design tools. This study highlights the utilization of CCTV Design Tools, specifically the System Design Tool (SDT), in designing surveillance systems in complex industrial environments. SDT is used to simulate camera coverage, identify blind spots, and determine the optimal configuration of the system. The case study was conducted at a metal smelting plant that has four crucial areas: Production Zone, Storage Warehouse, Loading Dock, and Access Door/Perimeter. Simulation results show that the use of SDT can increase surveillance coverage by 92.5%, reduce blind spots by 7.5%, and optimize the number of cameras required by 20%. With a technical data-driven approach and precise visualization of camera placement, SDT proved effective in improving the efficiency of surveillance system design. These findings confirm the importance of using simulation technology in the development of reliable, efficient, and field-appropriate industrial security systems.